Flavonoid Glycoside From Leucas lavandulaefolia Aerial Parts - Chandrashekhar, K.S.; Arun, B.J.; Satyanarayana, D. (Asian Journal of Chemistry, 2016)
In the present note, a flavonoid glycoside from Leucas lavandulaefolia aerial parts has been reported.